GAYA KEPEMIMPINAN PEREMPUAN TERHADAP KINERJA PEGAWAI DI KELURAHAN BANGKAI KECAMATAN WATANG PULU - Ayu Hartinah Zabila; Andi Astinah Adnan; Hariyanti Hamid (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
This study aims to determine the leadership style of female village heads on employee performance in Bangkai Village, Watang Pulu District, Sidenreng Rappang Regency.The population in this study were 30 stakeholders and a saturated sample of 30 people. This type of research is descriptive quantitative. Data collection techniques are observation, questionnaires (questionnaire) and library studies. The data analysis technique used is descriptive statistics.The results of this study indicate that the leadership style of the female village head with a value of 67% is categorized as